1992
DOI: 10.1111/j.1528-1157.1992.tb02193.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Neocorticectomy in Management of Intractable Epilepsy: Long‐Term Outcome and Predictive Factors

Abstract: We report the results of a long-term follow-up study of 50 patients who underwent removal of temporal neocortex with preservation of deeper limbic structures as surgical therapy for intractable temporal lobe epilepsy. The follow-up period ranged from 3 to 15 years. Preoperative EEG investigations were based on interictal discharges alone. Three factors were predictive of a good outcome: (a) A clear unilateral anterior-midtemporal focus (p less than 0.01), (b) stereotypical onset of temporal lobe seizure (p les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 19 publications
0
19
1
3
Order By: Relevance
“…An active program of epilepsy surgery has been established in Dublin since the early 1980s (5,6). This study considering the patients' aims for surgery started in 1994 when a psychiatrist was recruited to the program.…”
Section: Methodsmentioning
confidence: 99%
“…An active program of epilepsy surgery has been established in Dublin since the early 1980s (5,6). This study considering the patients' aims for surgery started in 1994 when a psychiatrist was recruited to the program.…”
Section: Methodsmentioning
confidence: 99%
“…One study considered students and persons in a sheltered workshop as being employed (10). Others relied on measures undefined (14,15) or subjective (11,(16)(17)(18) measures (e.g., work "ability," "capacity," "performance," or "career outcome.") Heretofore, only five studies (10,14,16,17,19) statistically analyzed their data, and only one (19) demonstrated significant improvement in unemployment rates.…”
Section: Discussionmentioning
confidence: 99%
“…Im Vergleich von Histologie und invasivem EEG mit Tiefenelektroden korreliert das Ausmaß von Zellverlust im CA1-Sektor des Hippokampus mit den iktalen Entladungen [17,27], während interiktale ETP im CA3-Sektor des Hippokampus entstehen [13,17].…”
Section: Diskussionunclassified
“…Grundsätzlich ist die Frage über die zu resezierenden anatomischen Strukturen bei TLE und über die Ausdehnung der Resektion seit langem kontrovers. Einige Zentren führen eine selektive Amygdalohippokampektomie durch [34], andere routinemäßig eine so genannte En-bloc-Standardresektion inklusive anteriorem und lateralem Temporallappen [6,25] oder nur eine Resektion des temporalen Neokortex mit Belassen der mesialen temporalen Strukturen [13]. In zwei Studien gab es signifikant bessere postoperative Ergebnisse mit ausgedehnter Resektion des mesialen Temporallappens [18,32], jedoch keine Korrelation mit der lateralen Ausdehnung der Resektion [18].…”
Section: Introductionunclassified